Botswana : Report on the Observance of Standards and Codes-Data Module-Response by the Authorities-Update. (IMF Staff Country Reports; Country Report ;, 2004)
This report on the Observance of Standards and Codes for Botswana highlights the Data Module and response by the authorities. National accounts are computed on an enterprise basis and where a full set of accounts is compiled. Data on financial accounts are captured but not fully analyzed because of the extent of errors in the data. Debt data are produced on an annual basis and published in the Annual Statements of Accounts.